2020
DOI: 10.25259/apos_14_2020
|View full text |Cite
|
Sign up to set email alerts
|

Index of Complexity, Outcome, and Need (ICON) in Dubai school-aged adolescents

Abstract: Objectives: The purpose of the study was to epidemiologically assess the prevalence of malocclusion and orthodontic treatment need in school-aged adolescents in Dubai using the Index of Complexity, Outcome, and Need (ICON). Null hypothesis tested was no significant differences in ICON scores among Dubai students as a function of gender or geographic/ethnic background. Materials and Methods: The sample was 17,763 adolescents with nearly equal by gender; India and the United Arab Emirates were represented abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Contrary to our ndings, some African studies, reported much lower estimates for Nigerian (13%) and Tanzanian children (22%) [20][21][22][23][24][25][26][27]. However, our results are in agreement with other local studies [28][29][30][31][32]. In terms of orthodontic treatment need, there was substantial agreement between the gold standard and the ICON index and thus the ICON index seems to be a viable Index to substitute the IOTN [33].…”
Section: Resultssupporting
confidence: 70%
“…Contrary to our ndings, some African studies, reported much lower estimates for Nigerian (13%) and Tanzanian children (22%) [20][21][22][23][24][25][26][27]. However, our results are in agreement with other local studies [28][29][30][31][32]. In terms of orthodontic treatment need, there was substantial agreement between the gold standard and the ICON index and thus the ICON index seems to be a viable Index to substitute the IOTN [33].…”
Section: Resultssupporting
confidence: 70%
“…The mean ICON score of all patients was 56.8 ± 13.5. The ICON score was 58.9 in South Asia, 57.3 in the United States, 56.6 in Australia, 55.8 in Africa, 52.4 in the Middle East, 50.3 in Europe, 47.2 in North and East Asia [ 29 ], and 44.6 in Iran [ 30 ]. Our data was similar to these scores.…”
Section: Discussionmentioning
confidence: 99%